Modified Binh Thuan bentonite as an efficient and recyclable catalyst fro the suzuki reaction between iodobenzene and phenylboronic acid - Son Nam et al, Phan Thanh (Vietnam Journal of Chemistry, 2014)
Modified Binh Thuan bentonite catalyst was prepared by exchanging with aqueous solution of PdCl2, affording a catalyst loading of 0.14 mmol of Pd/g (ICP-MS). The Pd2+-exchanged bentonite catalyst was assessed for its activity in the the Suzuki cross-coupling reaction between iodobenzene and phenylboronic acid to form biphenyl as the principal product. The reaction was performed using 0.2 mol% catalyst at 100oC in dimethylformamide (DMF) and in the presence of K3PO4 as a base, with biphenyl being formed in a conversion of up to over 95% (GC) without added phosphine ligands. It was also observed that the modified bentonite catalyst could be facilely separated from the reaction mixture by centrifugation or simple filtration, and could be reused in subsequent reactions without significant degradation in activity.